2019
DOI: 10.1108/jic-02-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

Strategic information disclosure, integrated reporting and the role of intellectual capital

Abstract: Purpose The purpose of this paper is to use a theoretical and empirical model to investigate the adoption of the integrated reporting (IR) framework as a strategic choice to signal intellectual capital (IC) to equity investors, with specific reference to the pharmaceutical industry. Design/methodology/approach The choice of drafting an integrated report is modelled as a means for managers to strategically disclose price-relevant information related to IC. The voluntary disclosure model developed by Verrecchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 67 publications
(89 reference statements)
0
24
0
Order By: Relevance
“…In relation to the determinants, Zuraida and Mulyany (2019), analysing 280 IPO prospectuses of Indonesian companies, found a positive and significant effect of year and firm size on ICD level. Other studies have analysed integrated reports (Abeysekera, 2013; Abhayawansa, Guthrie, & Bernardi, 2019; Beretta et al, 2019; Camodeca, Almici, & Sagliaschi, 2019; Casonato et al, 2018; Dumay, 2016; Dumay et al, 2019; Melloni, 2015; Terblanche & De Villiers, 2019; Veltri & Silvestri, 2015; Vitolla, Raimo, & Rubino, 2019b), but only two analysed the determinants of ICD. In this regard, Melloni (2015) highlighted how declining performance, the level of intangibles, and firm size influence the positive tone of ICD, while Beretta et al (2019) demonstrated the existence of a positive relationship between non‐financial performance and the optimistic tone of ICD.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…In relation to the determinants, Zuraida and Mulyany (2019), analysing 280 IPO prospectuses of Indonesian companies, found a positive and significant effect of year and firm size on ICD level. Other studies have analysed integrated reports (Abeysekera, 2013; Abhayawansa, Guthrie, & Bernardi, 2019; Beretta et al, 2019; Camodeca, Almici, & Sagliaschi, 2019; Casonato et al, 2018; Dumay, 2016; Dumay et al, 2019; Melloni, 2015; Terblanche & De Villiers, 2019; Veltri & Silvestri, 2015; Vitolla, Raimo, & Rubino, 2019b), but only two analysed the determinants of ICD. In this regard, Melloni (2015) highlighted how declining performance, the level of intangibles, and firm size influence the positive tone of ICD, while Beretta et al (2019) demonstrated the existence of a positive relationship between non‐financial performance and the optimistic tone of ICD.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Five papers published in this JIC special issue examine disclosure of IC through integrated reports and attributes of such disclosure. Camodeca et al (2019) directly address the debate publicly available information in other media. The authors conclude that the IR paradigm is being co-opted by impression management strategies to improve legitimacy through trust, reputation and social capital.…”
Section: External Reporting Of Icmentioning
confidence: 99%
“…The study assumes that integrated reports, when compliant with the International IR Framework, provide credible, precise and truthful information related to IC. The study, which focuses on the pharmaceutical industry, finds only companies with sufficient IC adopt integrated reporting, indicating that managers adopt the International IR Framework to signal companies' IC to the capital market.The study byTerblanche and De Villiers (2019) complementsCamodeca et al (2019) by examining whether integrated reports are associated with more IC disclosure and whether companies with greater exposure to capital markets as a result of being cross-listed in an…”
mentioning
confidence: 99%
“…The economic environment presented resembles the model economy described in Camodeca, Almici and Sagliaschi [118], where intellectual capital was a key variable to explain the risks underlying corporate performances. This study considers a similar approach in order to model companies operating in sectors where environmental safety and social spill-overs could instead largely affect business risks.…”
Section: Economic and Financial Environmentmentioning
confidence: 99%